PROFILE OF TETANUS IN CHILDREN AT PROF.KANDOU HOSPITAL 2002-2008 - Ayling Sanjaya; Novie Homenta Rampengan; Tommy Homenta Rampengan (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2013)
Backgrounds. Tetanus or lockjaw is an acute disease dwelling central nervous system caused by tetanoplasmin toxin produced by Clostridium tetani. Muscle spasm without consciousness disorder is distinguishing symptoms of tetanus. Tetanus in children remains as a health problem in developing countries including Indonesia.Objectives.  To study the profile of tetanus in children.Methods. Retrospective review of children diagnosed as tetanus at Prof. Dr. R.D.Kandou Hospital from 2002 to 2008. The datas were analyzed descriptively.Results.  There were 17 children with tetanus with age range 1-8 years, 12 males and 5 females. Seven of them had no tetanus immunization dan the rest of children with immunization never got booster immunization . Twelve children had otitis media and 5 children had untreated wound on their lower extremities as focus of infections. Period of getting wounded until symptoms appeared is approximately 3 days to 1 month.Common symptoms are trismus, convulsion, fever, opistotonus in all children. Complications such as bronchopneumonia occurred in 5 children, 4 children with severe tetanus and complications died in 19 hours to 18 days of treatment and the rest of 8 children had no complications.Conclusions.  Tetanus in children remains as health problem. Promoting prevention awareness in community and health providers is very important to decrease tetanus mortality and morbidity in children.